2022
DOI: 10.1109/access.2021.3137994
|View full text |Cite
|
Sign up to set email alerts
|

Successive Interference Cancellation Decoding With Adaptable Decision Regions for NOMA Schemes

Abstract: In this work, we propose adaptable decision regions in the successive interference cancellation (SIC) decoder for the three-user uplink/downlink non-orthogonal multiple access (NOMA) scheme by exploiting the knowledge of the channel gains. We present scenarios in which the modified SIC decoder outperforms the traditional one and is able to replicate the performance achieved by a deep learning-based decoder. We present analytical symbol error rate (SER) expressions for the three users, compare them to simulatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 24 publications
0
2
0
1
Order By: Relevance
“…Sequential Interference Cancellation (SIC) is a promising physical layer technique that can improve the efficiency of the wireless networks with relatively low additional complexity [41] . The idea of SIC is to sequentially decode all of the different users in the network by decreasing the error rate [42]- [43]. For the kth use, the instantaneous ratio s k between the received signal and noise at the kth receiving antenna where σ is the noise power of the Channel and P is the average received power expressed in watts is given by:…”
Section: System Modelmentioning
confidence: 99%
“…Sequential Interference Cancellation (SIC) is a promising physical layer technique that can improve the efficiency of the wireless networks with relatively low additional complexity [41] . The idea of SIC is to sequentially decode all of the different users in the network by decreasing the error rate [42]- [43]. For the kth use, the instantaneous ratio s k between the received signal and noise at the kth receiving antenna where σ is the noise power of the Channel and P is the average received power expressed in watts is given by:…”
Section: System Modelmentioning
confidence: 99%
“…The experimental results demonstrated that this receiver exhibited improved robustness against linear and non-linear distortions compared to receivers using SIC and joint detection. A modified SIC decoder was proposed to improve the symbol error rate performance of the three-user uplink/downlink NOMA by assuming channel gains, and the joint influence of the SNR and channel gains on the symbol error rate was also analyzed in [27]. Based on the above analysis, we can see that most existing works have focused primarily on designing signal detection algorithms at the receiver to improve error performance.…”
Section: Introductionmentioning
confidence: 99%
“…No caso de sistemas NOMA no domínio da potência, sinais de múltiplos usuários com diferentes níveis de potência são superpostos e a decodificação usual é realizada por cancelamento sucessivo de interferência (SIC, successive interference cancellation), na qual a decodificação é feita sucessivamente de acordo com as potências de cada usuário, que consideram os sinais de menor potência como ruído. Este método é eficiente quando existe uma suficiente separação entre as energias dos usuários [8]. Atratores caóticos tridimensionais possuem uma estrutura dinâmica associada a grafos e treliças que representa a evolução dinâmica das trajetórias caóticas no atrator.…”
Section: Introductionunclassified